2010
DOI: 10.1007/s00535-010-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lansoprazole on the expression of VEGF and cellular proliferation in a rat model of acetic acid-induced gastric ulcer

Abstract: One of the mechanisms of ulcer healing brought about by LPZ may be the involvement of endogenous prostaglandin (PG) secretion. The effect of endogenous PG secretion may be related to the induction of VEGF expression. On the other hand, LPZ administration increased MMP-2 expression, and this effect was not influenced by the inhibition of PG synthesis. The mechanisms of LPZ on ulcer healing may be involved by VEGF expression through endogenous PGs secretion. Additionally, the stimulated expression of MMP-2, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
7
1
1
Order By: Relevance
“…This is inconsistent with results from a study by Kobayashi et al[ 30 ] that showed that administration of lansoprazole (another proton pump inhibitor) led to increased expression of the VEGF gene in rats with gastric ulcers induced with acetic acid. These results suggest that proton pump inhibitors have an additional impact on protection of gastric ulcer formation ( i.e ., regulation of growth factor expression) other than prevention of gastric acid secretion[ 30 ]. However, this effect was not observed in our study using omeprazole, suggesting that not all proton pump inhibitors have the same effect on growth factors.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This is inconsistent with results from a study by Kobayashi et al[ 30 ] that showed that administration of lansoprazole (another proton pump inhibitor) led to increased expression of the VEGF gene in rats with gastric ulcers induced with acetic acid. These results suggest that proton pump inhibitors have an additional impact on protection of gastric ulcer formation ( i.e ., regulation of growth factor expression) other than prevention of gastric acid secretion[ 30 ]. However, this effect was not observed in our study using omeprazole, suggesting that not all proton pump inhibitors have the same effect on growth factors.…”
Section: Discussioncontrasting
confidence: 95%
“…Studies that evaluate the effect of tocotrienols on growth factor expression in gastric ulcers are limited. δ-tocotrienol has been shown to decrease the expression of VEGF in tumor cells, thereby reducing angiogenesis in these cells[ 30 - 32 ]. The tocotrienol administered in this study contained less than 4% δ-tocotrienol and consisted mostly of other isomers, the most being isomeric γ-tocotrienol (approximately 50%).…”
Section: Discussionmentioning
confidence: 99%
“…It is known from literature that lansoprazole strongly reduces the hydrogen ion release to gastric lumen, reducing then the ability of pepsin in damaging gastric mucosa and, consequently, preventing the injured area from acid and pepsin insults resulting in cell proliferation and healing (Kobayashi et al, 2010), most likely by activating the up-regulation of COX-2 additionally to its main antisecretory effect (Tsuji et al, 2002). Similarly, a study from our group had already demonstrated the cytoprotective properties of natural compounds accelerating the resolution of gastric ulcer by elevating PGs release as a consequence of COX-2 up-regulation (de-Faria et al, 2012a).…”
Section: Effect Of the Heab Oral Daily Treatment On Cicatrisation Andmentioning
confidence: 99%
“…This implied that MMP2 played a mechanistic role in generation of endostatin and angiostatin during duodenal ulceration. Recent studies have highlighted the function of MMPs as negative regulators of angiogenesis by their release of anti-angiogenic fragments, for example endostatin and angiostatin [35,[44][45][46][47], and two other studies have suggested that increased MMP2 may be important in the process of healing of rat gastric ulcer induced by acetic acid [48,49].…”
Section: Discussionmentioning
confidence: 99%